Echocardiographic Prediction of Left Ventricular Dysfunction After Transcatheter Patent Ductus Arteriosus Closure in Children - Hou, Miao; Qian, Weiguo; Wang, Bo; Zhou, Wanping; Zhang, Jianmin; Ding, Yueyue; Xu, Qiuqin; Huang, Jie; Shen, Jie; Cao, Lei; Lv, Haitao; Sun, Ling (Frontiers in Pediatrics, 2019)
Objectives To evaluate the change of left ventricular (LV) systolic function after transcatheter patent ductus arteriosus (PDA) closure in children, and to identify whether echocardiography parameters could be the predictors of LV dysfunction post-PDA closure if present. Methods 191 pediatric PDA patients were enrolled in this study, and they all underwent successful transcatheter PDA closure between January 2016 and December 2018. The patent ductus arteriosus diameter (PDAd), aortic root diameter (AOd), left atrial diameter (LAd), right ventricular outflow tract dimension (RVOT), LV end-diastolic dimension (LVEDD) and LV end-systolic dimension (LVESD) were measured by echocardiography at pre-closure, post-closure (within 24 hours after the procedure), and follow-up (3 months after the procedure). The ratio of PDAd to AOd (PDAd/AOd), the ratio of LAd to AOd (LAd/AOd), left ventricular ejection fraction (LVEF) and fractional shortening (FS) and were calculated. Results The LAd, LVESD, LVEDD, FS and LVEF significantly decreased in 24 hours after closure compared to pre-closure levels. However, all echocardiography parameters recover to pre-closure levels at 3 months after PDA closure in all patients. Moreover, the pre-closure LAd, LVEF, PDAd/AOd and LAd/AOd were higher in the patients with post-closure LV systolic dysfunction than those without post-closure LV systolic dysfunction. Furthermore, the pre-closure LVEF, PDAd/AOd and LAd/AOd were correlated with the post-closure LVEF, and pre-closure LVEF≤66.5%, PDAd/AOd≥0.28 as well as LAd/AOd≥1.54 predict the post-closure LV systolic dysfunction. Conclusion Transcatheter closure of PDA causes a significant decrease in LV systolic function early after PDA closure, which recovered completely within 3 months post-closure in children. Pre-closure LVEF, PDAd/AOd, LAd /AOd can be the predictors of post-closure left ventricular systolic dysfunction.